Zinc, zinc nanoparticles and plants - Sturikova, Helena; Krystofova, Olga; Huska, Dalibor; Adam, Vojtech (Journal of hazardous materials, 2018)
Zinc belongs to the mineral elements, the so-called micronutrients, which are essential for all types of plants. Embedding itself into the enzymes associated with proteosynthesis and energy processes, zinc is necessary for maintaining the integrity of biomembranes and also plays an important role in the development of seeds and generative organs. This review focuses on summarising the findings on the interaction of zinc and plants and translates into the knowledge of the effect of zinc nanoparticles on plants. The findings include an overview of both positive and negative effects on plants. In conclusion there is a great interest in nano-zinc as improving the knowledge about individual forms of zinc and their uptake and assimilation within higher plants may be the first step towards a wider involvement of zinc nanoparticles into agriculture.
Keywords: Environmental Pollutants; látky znečišťující životní prostředí; rostliny; Zinc; Nano-pesticides; Agriculture; nanotechnologie; zemědělství; Nanotechnology; Plants; půda; Nano-fertilizer; Growth; Toxicity; Development; zinek; Metal Nanoparticles; kovové nanočástice; Soil; Nanozinc